1995
DOI: 10.1002/path.1711750208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐myc protein is related to cell proliferation and expression of growth factor receptors in transitional cell bladder cancer

Abstract: Archival biopsy specimens from transitional cell bladder tumours (n = 185) were analysed immunohistochemically for expression of c-myc protein. The results were compared with histopathological and clinical parameters and survival. Forty-three per cent of the tumours were negative for c-myc protein and weak, moderate, or strong cytoplasmic expression was found in 34, 14, and 9 per cent of cases, respectively. Nuclear positivity for c-myc protein was detected in 35 per cent of tumours and nuclear positivity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 27 publications
4
28
1
2
Order By: Relevance
“…c-Myc has been detected previously in the cytoplasm of cell lines (Craig et al 1993) and tumor samples (Lipponen 1995;Pietilainen et al 1995;Boni et al 1998). In neurons, the detection of c-Myc in Purkinje cell cytoplasm parallels the observation that N-Myc, which is expressed in the nuclei of cerebellar Purkinje neurons during development, but localizes to Purkinje cell cytoplasm in adults (Wakamatsu et al 1993).…”
Section: Discussion Cdr2 Regulation Of the Transcription Factor C-mycsupporting
confidence: 53%
“…c-Myc has been detected previously in the cytoplasm of cell lines (Craig et al 1993) and tumor samples (Lipponen 1995;Pietilainen et al 1995;Boni et al 1998). In neurons, the detection of c-Myc in Purkinje cell cytoplasm parallels the observation that N-Myc, which is expressed in the nuclei of cerebellar Purkinje neurons during development, but localizes to Purkinje cell cytoplasm in adults (Wakamatsu et al 1993).…”
Section: Discussion Cdr2 Regulation Of the Transcription Factor C-mycsupporting
confidence: 53%
“…We also showed enhanced expression of c-myc at both mRNA and protein levels in androgen-treated cells. The c-MYC gene has indeed been found to correlate with the proliferation of bladder cancer cells (Lipponen 1995, Schmitz-Drager et al 1997. Androgen/AR-mediated upregulation of other Wnt targets, including cyclin-D1 (Wu et al 2010) and EGFR (Zheng et al 2011), has also been demonstrated in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lipponen [25] showed that 34% of patients had positive c-myc and they found that c-myc expression was associated with tumor grade but with no prognostic value. Nevertheless, c -myc proved in this study that it is actively engaged in the pathogenesis of bladder cancer due to many reasons; positive c -myc expression was found in 57% of patients, its association with tumor muscle invasion and it was significantly correlated positively with both p53 and Ki-67 proteins.…”
Section: Discussionmentioning
confidence: 99%